2006
DOI: 10.1111/j.1574-6968.2005.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopic study of the effects of ethanol on yeast cell surface morphology

Abstract: The detrimental effects of ethanol toxicity on the cell surface morphology of Saccharomyces cerevisiae (strain NCYC 1681) and Schizosaccharomyces pombe (strain DVPB 1354) were investigated using an atomic force microscope (AFM). In combination with culture viability and mean cell volume measurements AFM studies allowed us to relate the cell surface morphological changes, observed on nanometer lateral resolution, with the cellular stress physiology. Exposing yeasts to increasing stressful concentrations of etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
2
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 29 publications
(58 reference statements)
0
38
2
5
Order By: Relevance
“…It is also worth noting that despite a higher elasticity, the cell size and cell shape of ethanol-treated yeasts were similar to those of untreated yeast cells, suggesting that these parameters are likely dependent on cell wall composition. Our results thus differ from the previous work of Canetta et al (23), who actually reported shrinkage of cells after incubation for more than 1 h with ethanol at a 10% or higher concentration. That we did not observe such a shrinkage in our work can most likely be ascribed to the difference in the methods of immobilizing cells for AFM analysis, as our method kept the cells alive, whereas yeast cells were fixed and dried on a glass slide in the work of Canetta et al (23).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…It is also worth noting that despite a higher elasticity, the cell size and cell shape of ethanol-treated yeasts were similar to those of untreated yeast cells, suggesting that these parameters are likely dependent on cell wall composition. Our results thus differ from the previous work of Canetta et al (23), who actually reported shrinkage of cells after incubation for more than 1 h with ethanol at a 10% or higher concentration. That we did not observe such a shrinkage in our work can most likely be ascribed to the difference in the methods of immobilizing cells for AFM analysis, as our method kept the cells alive, whereas yeast cells were fixed and dried on a glass slide in the work of Canetta et al (23).…”
Section: Discussioncontrasting
confidence: 57%
“…It is therefore the best tool for visualizing and quantifying effects of ethanol stress at the single-cell level. This question was previously approached by Canetta et al (23). However, they used an air-drying immobilization technique to fix ethanol-treated yeast cells on a glass slide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Saccharomyces cerevisiae, also called baker's yeast, is the best-characterized eukaryotic model for scientific and biomedical research. Although the chemical composition of the yeast cell wall is well known, its molecular ultrastructure (organization or assembly) has not been extensively studied at nanoscale (4,5), although there are a few reports on the nanomechanical and adhesive properties of the yeast cell wall under native conditions or under stress conditions (6)(7)(8). As for Candida albicans, it is by far the most common human-pathogenic fungal species.…”
mentioning
confidence: 99%
“…Ethanol concentration can reach 10% in higher gravity fermentations, and acts especially upon biological membranes [35]. Reports showed ethanol effects in growth inhibition [45], lipid modification and loss of proton motive force across the membrane and increased membrane permeability/ fluidity [46]. Yet, cells exposed to oxygen, with high levels of sterols in membranes, and adequate levels of nutrients, amino acids and trace elements in the fermentation broth are able to respond efficiently to such effects [35].…”
Section: Yeast Physiologymentioning
confidence: 99%